The Perimeter of Financial Regulation - Zanforlin, Luisa (IMF Staff Position Notes; Staff Position Note, 2009)
The G-20 has called for a review of the scope of financial regulation. This call reflects concern that the coverage of prudential regulation has been too narrow. A discussion of extending the regulatory perimeter should, therefore, weigh carefully the experience of the past two years against these considerations. It will also be important to understand whether the assumptions underlying the existing regulatory model for banks are fatally flawed, or whether better regulation and supervision of the banks would be adequate. This set of proposals would represent a major increase in the scope of regulation of institutions, products, and markets. The proposals would best be taken forward as part of a broad program of financial sector reform, including the development of a macroprudential framework for assessing and managing systemwide risk. Even if new regulation is carefully designed to be proportionate to the risks in each new area, there will clearly be increased costs to the system. There would be an increased regulatory burden, which would also carry risks of unintended consequences. The current crisis has clearly shown that the cost of the alternative is also high.